Good clinical outcome for the majority of younger patients with hip fractures: a Swedish nationwide study on 905 patients younger than 50 years of age - Thoors, Oscar; Mellner, Carl; Hedström, Margareta (Acta Orthopaedica, 2021)
Background and purpose — Studies regarding hip frac- tures in young patients are rare since the patient population is small. We assessed clinical outcomes 4 months after hip fracture in patients < 50 years of age and whether there were differences between sexes and different age groups. Patients and methods — We included adult patients < 50 years with a hip fracture between January 1, 2014 and December 31, 2018. Baseline data were extracted from the Swedish Registry for Hip Fracture Patients and Treatment (RIKSHÖFT) and mortality data was obtained from Statis- tics Sweden. The outcome variables were change of walking ability, pain in fractured hip, use of analgesics, living condi- tions, and mortality rate at 4 months. Results — Of the 905 patients included, 72% were men and femoral neck fractures were most common (58%). 4 months after surgery, 23% used a walking aid and 7% reported severe pain. Women reported slightly more pain and higher usage of analgesics. Patients aged 40–49 reported higher usage of analgesics than patients aged 15–39, although the latter group reported more pain. Nearly all of those who lived independently before fracture did so at 4 months. The mortality rate was < 1%. Interpretation — Most patients did not use any walking aid and few had severe pain at 4 months. Furthermore, a hip fracture is not a life-threatening event in a patient < 50 years. The living conditions did not change for those who lived independently before the fracture.